Tarawangsa Padepokan Pusaka Lembur: Upaya Pengembangan Dalam Mempertahankan Seni Tarawangsa di Cangkuang Kabupaten Bandung - Sudarsono, Tarjo (LP2M ISBI Bandung, 2023)
Tarawangsa is a type of art that lives in an agrarian cultural ecosystem. Its existence cannot be separated from the lifestyle of the Sundanese people known as the people of the fields. One form of cultural expression between agrarian society and art, for example, can be found in the seren taun ceremony, ngalaksa. These ceremonies in particular have values related to the expression of people's gratitude for the produce of the earth, the harvest that nature has given to people's lives. In the Rancakalong Sumedang community, for example, some of these processes can still be found, especially in the ngalaksa ceremony procession. Apart from ceremonial activities related to an agrarian lifestyle, Tarawangsa also attends activities such as; the celebration of the birth of a baby and the ritual of treating the sick. This is because the agrarian lifestyle in some places tends to disappear, Tarawangsa is difficult to find in the context of agrarian rituals. One of these conditions can be found in Tarawangsa Cangkuang in Bandung Regency where its existence has further reduced the decline in the agrarian contextual function. Tarawangsa Cangkuang is not found in the ngalaksa ceremony, because in the people of Bandung Regency, it can hardly be found in the ngalaksa ceremony. Tarawangsa Cangkuang to a certain extent can only be found at the time of entertainment, and thanksgiving ceremonies for the birth of a baby. For this reason, development efforts are needed to maintain the existence of Tarawangsa Cangkuang. This paper is a record of participatory observation in recording the existence of Tarawangsa Cangkuang, as well as being involved in efforts to develop the show